2017
DOI: 10.1007/s00595-017-1586-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gender-based differences among surgeons in Japan: results of a survey conducted by the Japan Surgical Society. Part. 2: personal life

Abstract: The personal lives of Japanese surgeons differed significantly according to gender and whether they have children. The conservative idea that women should bear primary responsibility for the family still pertains for both men and women working as surgeons in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…The first theme, derived from one qualitative study (20 participants) 10 and ten quantitative cross-sectional surveys (183 to 6880 participants), 8,[11][12][13][14][15][16][17][18][19] was the influence of a medical career on decisions and priorities related to motherhood, including decisions about whether to have children, and when and how many, as well as the ongoing effect of a medical career on a woman's family (Supporting Information, table 2).…”
Section: Motherhood: the Impact Of Being A Doctor On Raising Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…The first theme, derived from one qualitative study (20 participants) 10 and ten quantitative cross-sectional surveys (183 to 6880 participants), 8,[11][12][13][14][15][16][17][18][19] was the influence of a medical career on decisions and priorities related to motherhood, including decisions about whether to have children, and when and how many, as well as the ongoing effect of a medical career on a woman's family (Supporting Information, table 2).…”
Section: Motherhood: the Impact Of Being A Doctor On Raising Childrenmentioning
confidence: 99%
“…Several studies found that a medical career could have a negative impact on family life and relationships. 8,[14][15][16][17]19 For example, two US studies identified that the working hours of women surgeons caused family strain; 16,17 another found that 2071 of 5582 female doctors (37%) believed that their career negatively affected relationships with their children. 15 Similarly, 36 of 91 female dermatologists with children (40%) felt that they had missed their children's milestones because of their careers.…”
Section: Motherhood: the Impact Of Being A Doctor On Raising Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…According to another survey on housework conducted by the Japan Surgical Society, male surgeons, with or without children, spent the same amount of time on housework. Female surgeons, with or without children, spent longer hours on housework than male surgeons (Kawase et al 2018). In that study, female surgeons aged 30 to 39 years with children spent the longest time on housework.…”
Section: Income Marriage and Parenthood Of Female Surgeons In Modermentioning
confidence: 72%